Consecration and Sacrifice in Ambrose and the Roman Canon. (September 2019) - Belcher, Kimberly Hope
Ambrose's interpretation of his eucharistic prayer played a foundational role in the developing theology of consecration in the West. Medieval commentators conflated Ambrose's prayer and ritual context with the later Roman Canon and the mass. By reconsidering the relationship between the eucharistic portions of De sacramentiis and De mysteriis and the structural differences between Ambrose's prayer and the earliest sacramentary versions of the Roman Canon, one can base a Western theology of the "sacrifice of praise and thanksgiving" on the Western eucharistic prayer family's chiastic references to offering and acceptance. Ambrose's witness overcomes ecumenical impasses on sacrifice, because the indigenous Western European theology of the Eucharistic Prayer includes the local community's participation in Christ's cosmic and ecclesial thanksgiving to God the Father; by this participation they bind themselves to do God's work; what is sacrificed is the greed by which they formerly sought their own interests. To constrain Roman Catholic theologies of the Roman Canon with this theology is also to respect Luther's testamentary theology of eucharistic liturgy and show a way for ecumenical convergence.